THE OVERVIEW OF PSYCHOLOGICAL PECULIARITIES OF GENDER IDENTITY - Vardanyan , N. T. (Արդի հոգեբանություն, 2018)
The article is dedicated to the review and analysis of gender identity development. We specifically focus on the concepts of masculine, feminine and androgyny types of gender identity and their definitions within different psychological theories.